The Role of the PGC1α Gly482Ser Polymorphism in Weight Gain due to Intensive Diabetes Therapy - Samir S. Deeb; John D. Brunzell (PPAR Research)
The Diabetes Control and Complications Trial (DCCT) involved intensive diabetes therapy of subjects with type 1 diabetes mellitus (T1DM) for an average period of 6.5 years. A subset of these subjects gained excessive weight. We tested for association of polymorphisms in 8 candidate genes with the above trait. We found the Gly482Ser polymorphism in the peroxisome proliferator-activated receptor γ coactivator-1α (PGC1α) to be significantly associated with weight gain in males (P=.0045) but not in females. The Ser allele was associated with greater weight gain than the Gly allele (P=.005). Subjects with a family history of type 2 diabetes mellitus (T2DM) were more common among those who gained excessive weight. We conclude that T2DM and the Gly482Ser polymorphism in PGC1α contribute to the effect of intensive diabetes therapy on weight gain in males with T1DM.